DESKRIPSI DAMPAK GEMPA BUMI DAN LIKUIFAKSI TERHADAP PETANI DI DESA JONO OGE KABUPATEN SIGI PROPINSI SULAWESI TENGAH - Karlina Muhsin Tondi (Universitas Tadulako, 2019)
The purpose of this study was to describe the impact of earthquakes and liquefaction on farmers in Jono Oge village, Sigi regency, Central Sulawesi province. This research was a qualitative descriptive study using questionnaire and interview instruments. Information was also obtained through literature study and field observations. The subjects of this study were farmers in Jono Oge village, Sigi regency. Respondents were purposively selected. The questionnaires consisted of ten questions which had been validated by experts. The questionnaires were given to ten farmers while the interview was conducted on four farmers. The literature study was carried out by tracing information on the Sigi Regency BPS Office, Jono Oge Village Office and a number of online media reporting on earthquakes and liquefaction that occurred in Central Sulawesi on 28 September 2018. The observations were made on such land affected by earthquakes and liquefaction. These observations were also carried out on irrigation channels and cultivated land in the area of liquefaction. It was found that around 250 ha cultivated agricultural land had been destroyed due to the liquefaction as well as the irrigation canals used to distribute water to the cultivated land had been damaged. The disappearance of the cultivated land had led the farmers to rent agricultural land in the nearby villages such as Lolu, Sidera and Pombewe in order for them to sustain their livelihood. The source of water for irrigation was ground water pumping by Alcon equipment donated by several organizations. The farmers' income was also decreased by almost 50%. Thus it was concluded that the earthquake and liquefaction had a significant impact on the lives of farmers in Jono Oge Village. Keywords: Earthquakes, Farmers, Jono Oge and Liquefaction.